2012
DOI: 10.1097/dcr.0b013e3182695115
|View full text |Cite
|
Sign up to set email alerts
|

Colectomy for Endoscopically Unresectable Polyps

Abstract: The finding that polyp size and villous features do not strongly predict malignancy differs from previous endoscopic studies. This study confirms that polyps located in the left colon or with high-grade dysplasia are more likely to harbor cancer. The results of this study suggest that endoscopically unresectable polyps are best treated by radical oncologic resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 20 publications
2
38
0
2
Order By: Relevance
“…One might assume this rate to be higher in other clinics, as our centre is a TIEC with large experience in removing large adenomas endoscopically. The distribution of nonmalignant polyps referred for surgery in this study revealed a majority of polyps located on the right side, in accordance with the findings in other series of laparoscopic colectomy for polyps . This may reflect the reluctance of endoscopists to resect large and difficult polyps in the right colon because of the fear of complications such as perforation of the relatively thin right colonic wall .…”
Section: Discussionsupporting
confidence: 90%
“…One might assume this rate to be higher in other clinics, as our centre is a TIEC with large experience in removing large adenomas endoscopically. The distribution of nonmalignant polyps referred for surgery in this study revealed a majority of polyps located on the right side, in accordance with the findings in other series of laparoscopic colectomy for polyps . This may reflect the reluctance of endoscopists to resect large and difficult polyps in the right colon because of the fear of complications such as perforation of the relatively thin right colonic wall .…”
Section: Discussionsupporting
confidence: 90%
“…In the literature review by Bertelson et al [23], the proportion of cancer found in surgically treated polyps ranged from 0 to 36%. The 44.4% proportion of operative specimens with changes of malignancy or pre-malignancy in this series demonstrated good case selection by attending physicians and justified the volume of operations performed.…”
Section: Discussionmentioning
confidence: 99%
“…Tubulo-villous adenomas are at intermediate risk (22%). One recent study, however, did not identify size and histological sub-type as risk factors for development of cancer in polyps [8]. By definition, all types of adenomas exhibit some degree of dysplasia, meaning abnormal glandular architecture and damaged intracellular structures.…”
Section: Neoplastic Colorectal Polypsmentioning
confidence: 99%
“…Nevertheless, it is important to note that a partial colectomy for removing a polyp that is not amenable to colonoscopic resection is potentially a procedure for treating cancer. A recent large-scale study (750 patients) actually found that the incidence of cancer in patients undergoing colectomy for an irretrievable polyp is 17.7% [8]. Multivariate analysis identified two risk factors for the polyps harboring cancer: polyp location at the left colon and the presence of high grade dysplasia.…”
Section: Treatment Of Neoplastic Colonic Polypsmentioning
confidence: 99%